Positive parity pentaquark towers in large N(c) QCD. - Pirjol. Dan (2007)
We construct the complete set of positive parity pentaquarks, which correspond in the quark model to sq Nc 1 states with one unit of orbital angular momentum L 1. In the large Nc limit they fall into the K 1=2 and K 3=2 irreps (towers) of the contracted SU4 c symmetry. We derive predictions for the mass spectrum and the axial couplings of these states at leading order in 1=Nc. The strong decay width of the lowest-lying positive parity exotic state is of order O1=Nc , such that this state is narrow in the large Nc limit. Replacing the antiquark with a heavy antiquark Qq Nc 1, the two towers become degenerate, split only by O1=mQ hyperfine interactions. We obtain predictions for the strong decay widths of heavy pentaquarks to ordinary baryons and heavy H Q mesons at leading order in 1=Nc and 1=mQ.